Eosinophilic Granuloma Involving Lower Cervical Spine - ULU, Mustafa Onur; CANBAZ, Bülent; KEMERDERE, Rahşan; TANRIVERDİ, Taner (Cerrahpaşa Medical Journal, 2014)
Langerhans cell histiocytosis is a rare disorder of pediatric age group, characterized by the clonal proliferation and infiltration of organs by the Langerhans cells. Infiltration of bone with these cells causing an osteolytic tumor-like lesion is called an eosinophilic granuloma. Spinal involvement of eosinophilic granuloma is rare and predominantly thoracal or lumbar. Cervical involvement in an adult patient is even rarer. Many treatment modalities are being used for spinal EG, but the appropriate management is still controversial. In this 28 years old patient presented, who was harbouring mass located in the corpus of C5 vertebra, the lesion was totally excised and postoperatively rapid relief of symptoms was observed. No recurrance was detected on the post operative 3rd and 7th month control cervical MRI's. Although EG is rarely encountered in cervical vertebrae, it must be considered in the differential diagnosis among the pathological lesions in that region. Surgery provides rapid and effective results and with close follow up, the need for adjuvant therapies can be minimized and their hazardous side effects can be avoided.